Investor sentiment in the US-dollar: longer-term, nonlinear orientation on PPP - Lukas Menkhoff; Rafael R. Rebitzky (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
How is it possible that exchange rates move in the long run towards fundamentals, while professionals form consistently irrational exchange rate expectations? We look at this puzzle from a different perspective by analyzing investor sentiment in the US-dollar market. First, long-horizon regressions show that investor sentiment is connected with exchange rate returns at longer horizons, i.e. more than two years. Second, sentiment is cointegrated with fundamentals, whereas third, this relation becomes stronger, the larger exchange rate's misalignment from long-run PPP. In sum, investor sentiment's behavior in the US-dollar market closely matches with established facts of empirical exchange rate research.
Keywords: F31; G14; 330; Exchange rates; investor sentiment; long-horizon regression; threshold VECM; Wechselkurs; Kaufkraftparität; Anlageverhalten; Erwartungstheorie; Schätzung; Theorie; USA